Longitudinal evaluation of perceived stress and memory complaints in the Einstein Aging Study. Issue 1 (2nd January 2021) - Bell, Tyler; Hill, Nikki; Mogle, Jacqueline; Sweeder, Logan; Bhargava, Sakshi
ABSTRACT: Background: Perceived stress decreases memory performance and escalates the risk of developing cognitive impairment. Despite these concerning cognitive outcomes, longitudinal assessment of the relationship between perceived stress and memory complaints within a racially diverse sample remains scant. Method: 391 cognitively intact older adults ( M = 77.31, SD = 4.75) from the Einstein Aging Study were measured annually for up to nine years. Memory complaint items included self-reported frequency of forgetfulness, one-year memory decline, and 10-year memory decline. Multilevel models examined between-person and within-person associations between perceived stress and memory complaints while controlling for demographic differences and neuroticism. Results: Strong between-person associations emerged such that older adults with generally higher perceived stress were more likely to report memory complaints, and vice versa. No significant concurrent within-person associations emerged. One lagged association emerged showing that within-person increases in perceived stress translated to a higher likelihood of reporting 10-year memory decline at the next annual screening. Conclusion: Older adults with higher perceived stress are at risk for memory complaints over time. Further research into the relationship between perceived stress and memory complaints is necessary to augment our understanding of how risk factors of cognitive decline present throughout the aging process.